Patient Experience and Satisfaction with Orthopedic Services at a Community (Rural) Setting Hospital-How Is It Different from Urban Setting - Khalid Hasan; Shahin Kayum (Taylor & Francis Group, 2024)
Patient experience and satisfaction are the keystones in evaluating the effectiveness of clinical care in musculoskeletal medicine. Although all orthopedic settings work on the same principles of providing safe and quality health care, community hospitals represent a unique environment. There may be key differences with regard to patient experience between these settings. Accessibility to care, choices of provider, personalized care, availability of and access to resources, cultural and social variances, and waiting times are a few of the many elements that may impact patient experience and satisfaction. This narrative review aims to explore the core differences in these settings and how they can reflect on patient experience and satisfaction.